Sinologists as translators in the seventeenth to nineteenth centuries - Führer, Bernhard, 1960-; Wong, Wang-chi, 1956- (Asian translation traditions series, 2015)
This collection deploys archive studies and translation hermeneutics to merge the historical study of sinology with translation research. Focusing on the context of contributions by early Sinologists and their translations of works in Chinese, the essays in this volume ask why certain works were chosen for translation in particular historical moments; how they were interpreted, translated, and manipulated; and what influence they had, especially in advancing sinology in various countries. This book reconstructs a wider historical and intellectual context from which certain translations emerged and further expands sinology through the extensive use of overlooked archive materials.